The Relationship Between Knowledge And Attitudes Towards Prevention Of Sexually Transmitted Infections (STIS) Among Adolescents In Sumbersari Village, Kepahiang Regency - Nimas Ayu Lestari Nurjanah; Alifani Faiz Faradhila (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Sexually transmitted infections (STIs) remain a significant reproductive health problem among adolescents, especially in rural areas with limited access to health information. Adequate knowledge about STIs is expected to shape positive attitudes toward prevention efforts. This study aims to determine the relationship between knowledge and attitudes toward STI prevention among adolescents in Sumbersari Village, Kepahiang District.This study used a quantitative design with a cross-sectional approach. The study sample consisted of 38 adolescents, selected using total sampling technique. Data were collected using a structured questionnaire that measured the level of knowledge and attitudes toward STI prevention. Data analysis was performed univariately to describe the frequency distribution and bivariately using the Chi Square test with a significance level of α = 0.05.The results showed that most respondents had good knowledge about STIs (50.0%) and positive attitudes toward STI prevention (63.2%). The Chi-Square test results showed a significant relationship between knowledge and attitudes toward STI prevention among adolescents (p-value = 0.013). Adolescents with better knowledge tended to have more positive attitudes toward STI prevention than adolescents with less knowledge.The conclusion of this study shows that knowledge plays an important role in shaping attitudes toward STI prevention among adolescents. Therefore, continuous and contextual efforts to improve adolescent reproductive health education are needed, especially in rural areas, to support effective STI prevention.